Limitaciones del fiscal como director de la investigación del delito en la provincia de Trujillo 2007 – 2012 - Aguirre Bazán, Luis Alberto (2013)
The prosecution accused without sufficient evidence, without adequate research strategy and driven by the desire to gain unwarranted abuse of the right if her competence, which is why we have investigated the performance of the prosecutor in his role as director of criminal investigation under the new Criminal Procedure Code (NCPP) province of Trujillo, from 2007 to 2012 in order to identify possible circumstances or conditions that limit their research; so that the following problem is formulated What are the limitations of the tax as director of criminal investigations in the province of Trujillo from 2007 to 2012?, which posed the following hypothesis: “The limitations of the prosecutor as director of criminal investigations in the province of Trujillo from 2007 to 2012 are the lack of objectivity, the remnants of an inquisitorial system, professional training gaps and breach of the principle of legality”. Existing background of the topic, but not with respect to the formulated problem, we performed a theoretical framework that defines the legal concepts of the Preliminary Investigation and Research School and the role of the prosecutor in the research, all under the parameters of the new Code of Criminal 2004. In order to solve the problem posed in this investigation hermeneutic method was used for the analysis of doctrine and criminal proceedings with respect to the prosecutor's role as director of research in order to compare their work in practice and what established doctrine. For the analysis of the legislation of the NCPP exegetical method was used which consisted of comparing the tax work done and what Peruvian criminal law prescribes. For data collection technique was used to interview to obtain valid and reliable responses of the judges, prosecutors and lawyers and documentary collection technique that consisted of extracting data from judicial processes where applied New Criminal Procedure Code. Finally arises the corresponding conclusions, one being generally that no objectivity on the part of prosecutors, the remnants of an inquisitorial system, the deficiency in training, the breach of the principle of legality are limitations of the prosecutor in his role as director of criminal investigations in the province of Trujillo from 2007 to 2012.